2010
DOI: 10.4049/jimmunol.0902444
|View full text |Cite
|
Sign up to set email alerts
|

CXC Chemokine Ligand 2 Induced by Receptor Activator of NF-κB Ligand Enhances Osteoclastogenesis

Abstract: CXCL2 has been known to regulate immune functions mainly by chemo-attracting neutrophils. In this study, we show that CXCL2 can be induced by receptor activator of NF-κB ligand, the osteoclast (OC) differentiation factor, through JNK and NF-κB signaling pathways in OC precursor cells. CXCL2 in turn enhanced the proliferation of OC precursor cells of bone marrow-derived macrophages (BMMs) through the activation of ERK. Knockdown of CXCL2 inhibited both the proliferation of and the ERK activation in BMMs. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
59
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 23 publications
10
59
1
Order By: Relevance
“…Leukemia inhibitory factor regulates the commitment of CSCs to the endothelial cell lineage, contributing to revascularization in the process of tissue remodeling and/or regeneration (59). The CXCL family chemokines play important roles in promoting stem cell migration and homing through JNK and NFB signaling pathways (60,61). Among them, EGF, BMP3, and the FGF family cytokines are essential for stem cell survival and proliferation (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Leukemia inhibitory factor regulates the commitment of CSCs to the endothelial cell lineage, contributing to revascularization in the process of tissue remodeling and/or regeneration (59). The CXCL family chemokines play important roles in promoting stem cell migration and homing through JNK and NFB signaling pathways (60,61). Among them, EGF, BMP3, and the FGF family cytokines are essential for stem cell survival and proliferation (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Among the other secreted signaling molecules showing drastic differences in expression was the gene encoding the chemokine Cxcl2 (32-fold upregulated in susceptible mice). This chemokine plays a major role as a neutrophil attractant and has been implicated in certain inflammatory diseases (14). It would be of interest to investigate if this molecule might have a role in the progression of ECM, especially given its elevated expression.…”
Section: Resultsmentioning
confidence: 99%
“…groβ could activate the sphingomyelin pathway or Jnk1 and induced apoptosis in proliferating cells (21)(22). groβ also induce the activation of mek/erk signal pathway and promote cell proliferation (15,20,21,23). However, little is known about the relationship between groβ and chemotherapeutic agent-induced apoptosis.…”
Section: Groβ and Its Downstream Effector Egr1 Regulate Cisplatin-indmentioning
confidence: 99%
“…our result showed that inhibition of expression of groβ by rnA interference could decrease cisplatin-induced apoptosis in WHco1 cells. groβ was reported to activate many signal pathways, such as Jnk (21,22) and mek/erk signal pathway (15,20,21,23). many of these pathways were correlated to cisplatin-induced apoptosis.…”
mentioning
confidence: 99%